Economic reforms and poverty reduction / edited by A. Santhosh Mathew and Mark A. Robinson - "Mathew, A Santhosh.(ed.)" (New Delhi, 2000)
This book examines the relationship between economic reforms and poverty reduction in India over the past decade, with a particular emphasis on the poverty consequences of liberalisation and expenditure controls in the 1990s. Drawing on the perspectives of academics and government practitioners involved in the reform process, the book seeks to contribute to policy debates on the implications of economic liberalisation for poverty reduction strategies in the context of administrative reforms. Contributions range from poverty measurement and targeting, through to the poverty impact of economic reforms, national and international experiences with poverty reduction, and the changing nature of public administration. By focusing on the government's investments in anti-poverty programs and the mixed effects of official policies on the livelihoods of the poor, the book provides a useful corrective to analyses that focus exclusively on macro economic reforms. The volume will be of interest to policy makers, academics, students and practitioners concerned with contemporary development issues in India.
Keywords: Economic reforms - India